Straightforward synthesis of gold nanoparticles by adding water to an engineered small dendrimer - Gottis, Sébastien; Laurent, Régis; Collière, Vincent; Caminade, Anne-Marie (Beilstein Journal of Nanotechnology, 2020)
A small water-soluble phosphorus-containing dendrimer was engineered for the complexation of gold(I) and for its reduction under mild conditions. Gold nanoparticles were obtained as colloidal suspensions simply and only when the powdered form of this dendrimer was dissolved in water, as shown by transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX) analyses. The dendrimers acted simultaneously as mild reducers and as nanoreactors, favoring the self-assembly of gold atoms and promoting the growth and stabilization of isolated gold nanoparticles. Thus, an unprecedented method for the synthesis of colloidal suspensions of water-soluble gold nanoparticles was proposed in this work.
Keywords: colloidal suspension; complexation; dendrimer; gold nanoparticle; phosphorus